Exploring the landscape pattern change analysis for the transboundary Nyungwe-Kibira Forest (2000–2019): a spatially explicit assessment - Udahogora, Madeleine; Zhaoping, Yang; Fang, Han; Kayumba, Patient Mindje; Mind’je, Richard (Frontiers in Forests and Global Change, 2024)
Protecting and restoring forest ecosystems is crucial to preserve ecological functionality in deforested or degraded landscapes. However, high human pressure on forests, inadequate conservation measures, and a lack of community engagement pose challenges to forests in developing nations. We explored the utility of remote sensing datasets to analyze landscape change in the transboundary Nyungwe Kibira forest between 2000-2019, highlighting the need to comprehend the dynamics and vulnerability of this ecosystem to support restoration initiatives. The landscape cover is in flux with some regions experiencing gains, others losses. Analysis indicates substantial increase in built-up (+62.3%) and cropland (+18.07%) areas, resulting in a gross change of 14,133 ha and 6,322 ha, respectively. This expansion is significant as built-up areas have extended from the buffer zone towards the forest along the northwestern edge of Rwanda. Despite an overall forest gain of 9.11%, deforestation of -14,764 ha indicates a net loss of 6.92%. Rapid expansion of human-made land uses causes these changes. Built-up areas account for the majority (33.02%) of net forest loss in the northern edge of Rwanda. Cropland expansion contributes to a net forest loss (-9.48%), most significantly in the southeast in Burundi. The forest is predicted to decrease 0.74% by 2030. Current analysis shows the Nyungwe Kibira forest undergoing transformations, with aggregated forest and cropland (66% and 7%), dissected rangeland (24%), and created built-up areas (3%). These findings suggest prioritizing mitigation plans to restore the forest.